Sofrimento psíquico em psicólogos que atuam no contexto organizacional: um estudo na cidade de Uberlândia - Pereira, Maristela de Souza (2005)
This paper investigates on the job pleasure and suffering experienced by psychologists who work in organizations. The purpose is to analyze the strategies, used by organizational psychologists in psychic suffering, to deal with this situation and be able to keep at its work. The theoretical perspective adopted is that the work is both a source of pleasant experiences as well as suffering and that each individual finds specific ways to deal with the reality that he/she goes through, and meanwhile also uses confrontation strategies that are common in the organizational field. Both the suffering and the pleasure, as psychic experiences, can happen in different ways, and two indicators of suffering, grief and anxiety were adopted. Also, two indicators of pleasure, value and acknowledgement, were adopted. It was used the qualitative method and two individuals as identification objects for the measurement in the On The Job Pleasure and Suffering Scale. Based on the results found, individual semiguided interviews were conducted with two psychologists who went through significant suffering on the job. According to the results, both psychologists found sources of pleasure and suffering on the job, and used confrontation strategies to keep their psychic health. These finds show that even individuals who have a significant activity and with a certain autonomy and choice possibilities, also suffer the impact of the work organization. Moreover, the work in a company can be perceived by the psychologist as distant from his/her education and he/she cannot show totally all his/her knowledge and skills acquired in the under graduate course.